Evaluation of alternate lines of Fe for sequential multi-element determination of Cu, Fe, Mn and Zn in soil extracts by high-resolution continuum source flame atomic absorption spectrometry - Raposo Junior, Jorge Luiz [UNESP]; de Oliveira, Silvana Ruella [UNESP]; Caldas, Naise Mary [UNESP]; Gomes Neto, José Anchieta [UNESP] (Elsevier B.V., 2008)
The usefulness of the secondary line at 252.744 nm and the approach of side pixel registration were evaluated for the development of a method for sequential multi-element determination of Cu, Fe, Mn and Zn in soil extracts by high-resolution continuum source flame atomic absorption spectrometry (HR-CS FAAS). The influence of side pixel registration on the sensitivity and linearity was investigated by measuring at wings (248.325, 248.323, 248.321, 248.329, and 248.332 nm) of the main line for Fe at 248.327 nm. For the secondary line at 252.744 nm or side pixel registration at 248.325 nm, main lines for Cu (324.754 nm), Mn (279.482 nm) and Zn (213.875 nm), sample flow-rate of 5.0 mL min(-1) and calibration by matrix matching, analytical curves in the 0.2-1.0 mg L-1 Cu, 1.0-20.0 mg L-1 Fe, 0.2-2.0 mg L-1 Mn, 0.1-1.0 mg L-1 Zn ranges were obtained with linear correlations better than 0.998. The proposed method was applied to seven soil samples and two soil reference materials (IAC 277; IAC 280). Results were in agreement at a 95% confidence level (paired t-test) with reference values. Recoveries of analytes added to soil extracts containing 0.15 and 0.30 mg L-1 Cu, 7.0 and 14 mg L-1 Fe, 0.60 and 1.20 mg L-1 Mn, 0.07 and 0.15 mg L-1 Zn, varied within the 94-99, 92-98, 93-101, and 93-103% intervals, respectively. The relative standard deviations (n = 12) were 2.7% (Cu), 1.4% (Fe - 252.744 nm), 5.7% (Fe - 248.325 nm), 3.2% (Mn) and 2.8% (Zn) for an extract containing 0.35 mg L-1 Cu, 14 mg L-1 Fe, 1.1 mg L-1 Mn and 0.12 mg L-1 Zn. Detection limits were 5.4 mu g L-1 Cu, 55 mu g L-1 Fe (252.744 nm), 147 mu g L-1 Fe (248.325 nm), 3.0 mu g L-1 Mn and 4.2 mu g L-1 Zn. (C) 2008 Published by Elsevier B.V.
Keywords: Micronutrients; Soil; High-resolution continuum source flame atomic spectrometry; Side pixel registration